Economic and Environmental Assessment of Low-Carbon Concrete Using Rice Husk Ash and Steel Industry By-Products: Toward Sustainable and Circular Construction - Wegig Husain Robbiardi (PT Advanced business journal, 2025)
The cement sector accounts for approximately 7–8% of global anthropogenic CO₂ emissions, posing both environmental and financial challenges to achieving carbon-neutral construction. This study evaluates the techno-economic and environmental feasibility of low-carbon concrete incorporating rice husk ash (RHA) and steel industry by-products—ground-granulated blast-furnace slag (GGBFS) and steel slag (SS)—as partial substitutes for ordinary Portland cement (OPC). Experimental mixes with 10–30% binder substitution were tested for compressive strength, durability, and microstructural performance, while a cradle-to-gate life-cycle assessment (LCA) quantified the environmental and cost impacts in accordance with ISO 14040/44 standards. The optimal blend (10% RHA + 15% GGBFS + 5% SS) achieved ≈46 MPa 28-day compressive strength— 8% higher than OPC—and exhibited enhanced chloride resistance. LCA results revealed 30% lower global-warming potential (GWP), 20% lower acidification potential (AP), and an estimated 15% reduction in production cost per cubic meter of concrete. These improvements strengthen the financial case for low-carbon materials by reducing carbon liabilities, improving resource efficiency, and aligning with sustainable investment frameworks under the UN SDG 12 and EU Taxonomy for sustainable activities. The findings provide evidence-based insights for policymakers, investors, and construction firms seeking to integrate material innovation into green finance and circular economy strategies.